PENERAPAN METODE MUTQIN DALAM MENINGKATKAN KUALITAS MENGHAFAL AL-QUR'AN DI PONDOK PESANTREN MODERN AL AZHAR GRESIK - Naufal Farras; Kasuwi Saiban; Umi Salamah (STKIP Subang, 2026)
This study aims to describe and analyze the implementation of the Mutqin Method in improving the quality of Al-Qur'an memorization at Pondok Pesantren Modern Al Azhar Gresik and its implications. This research uses a qualitative case study approach. Data were collected through interviews, observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana. The results show that: (1) The Mutqin Method is implemented through three stages: planning, which involves setting learning objectives, methods, and scheduling; implementation, which involves executing the plan and running active learning processes using the Mutqin method; and evaluation, which focuses on assessing learning outcomes in terms of both quality and quantity as well as the effectiveness of the method used. (2) The implications of implementing the Mutqin Method are: first, an improvement in the ability to strengthen Al-Qur'an memorization correctly; and second, an improvement in comprehension skills covering verse position, surah type, surah name, page number, and asbabun nuzul. This research confirms that the Mutqin Method is an effective approach for improving the quality and strength of Al-Qur'an memorization in a pesantren setting. Keywords: Mutqin Method, Learning Implementation, Al-Qur'an Memorization, Islamic Boarding School